Synergizing Functional Safety and Cybersecurity Assurance in Autonomous Driving Platforms: A Multi-Dimensional Framework for Fault-Tolerant Architectures and Regulatory Compliance - Elena Hoffman (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The rapid integration of autonomous driving technologies into the global transport infrastructure has necessitated a fundamental rethinking of how safety-critical systems are designed, validated, and maintained. This research provides an extensive exploration of the convergence between functional safety, as dictated by standards such as IEC 61508, and cybersecurity assurance in modern automotive zonal controllers. By examining the theoretical foundations of fault-tolerant systems, including All Voting Triple Modular Redundancy (AVTMR) and dual-duplex lockstep architectures, the article delineates the technical requirements for achieving Safety Integrity Level 4 (SIL-4) in complex hardware environments. Furthermore, the study addresses the critical challenge of managing security evidence within agile software development lifecycles, advocating for a cross-project classification approach to identify security-related requirements in diverse regulatory documents. Through the application of micro Markov models for quantitative safety assessment and the analysis of information security culture, this work establishes a comprehensive methodology for synthesizing hardware reliability with robust security assurance cases. The findings highlight the necessity of a flexible scheduling architecture for resource distribution in autonomous platforms, ensuring that both safety and security requirements are met without compromising system performance. This article serves as a definitive guide for researchers and practitioners in developing dependable, secure, and compliant intelligent transportation systems.